Spark, trauma and the novel. Issue 9 (21st October 2018) - Cheyette, Bryan
ABSTRACT: What is clear from even a cursory reading of Muriel Spark's dazzling and cunning fictions is that she engages with a bewildering range of literary modes but only in so far as they can be subsumed by her singular vision. Spark's quirky and playful voice refuses to be contained by any one doctrine or identity. First among the philosophies and identities which she finds absurd is that of the conventional realist novel with its humanist assumptions that the plot of a novel, with the individual at its heart, can be confused with life. This essay will juxtapose Spark's scepticism in relation to the conventional novel form with the fierce self-protection of her life-story (before she was a novelist) which she, paradoxically, refigures in many of her imaginative works. The focus is on her fictions set in Africa where she felt at her most vulnerable as the potential object of various 'shooting affairs'. It will show the ways in which she redeems such trauma in her late fiction. In the dismissal of the human-centred realist novel, and the fantasy that individuals can control the world, Spark, is equally anarchic and orthodox; playful and controlling.